MONGOLIAN BEKS UNDER UMARSHAIKH MIRZA - Makhmudov Uktamjon Mukhsinjan ugli (Western European Studies, 2024)
In this article, general comments are made about the Mongolian begs who served Umarshaikh Mirza, the father of Zahiriddin Muhammad Babur, and about their activities during the time of Babur
Keywords: Umarshaikh Mirza; Babur; Mongol begs